LEGAL PROTECTION FOR HEIRS REGARDING INHERITANCE OF LAND OWNERSHIP RIGHTS THAT HAVE NOT BEEN REGISTERED AT THE JAYAPURA REGENCY LAND OFFICE - Solossa, Marthinus; Yoseph Palenewen, James; Tanati, Daniel (Penerbit Lafadz Jaya, 2025)
The research, entitled